CYP153A6, a Soluble P450 Oxygenase Catalyzing Terminal-Alkane Hydroxylation - Funhoff, Enrico G. (American Society for Microbiology, 2006)
The first and key step in alkane metabolism is the terminal hydroxylation of alkanes to 1-alkanols, a reaction catalyzed by a family of integral-membrane diiron enzymes related to Pseudomonas putida GPo1 AlkB, by a diverse group of methane, propane, and butane monooxygenases and by some membrane-bound cytochrome P450s. Recently, a family of cytoplasmic P450 enzymes was identified in prokaryotes that allow their host to grow on aliphatic alkanes. One member of this family, CYP153A6 from Mycobacterium sp. HXN-1500, hydroxylates medium-chain-length alkanes (C(6) to C(11)) to 1-alkanols with a maximal turnover number of 70 min(−1) and has a regiospecificity of ≥95% for the terminal carbon atom position. Spectroscopic binding studies showed that C(6)-to-C(11) aliphatic alkanes bind in the active site with K(d) values varying from ∼20 nM to 3.7 μM. Longer alkanes bind more strongly than shorter alkanes, while the introduction of sterically hindering groups reduces the affinity. This suggests that the substrate-binding pocket is shaped such that linear alkanes are preferred. Electron paramagnetic resonance spectroscopy in the presence of the substrate showed the formation of an enzyme-substrate complex, which confirmed the binding of substrates observed in optical titrations. To rationalize the experimental observations on a molecular scale, homology modeling of CYP153A6 and docking of substrates were used to provide the first insight into structural features required for terminal alkane hydroxylation.